Judging orthodontic treatment complexity - Clijmans, Maïté (Dental Press J Orthod, 2016)
OBJECTIVE: The aim of the present study was to investigate possible relations between anticipated overall treatment complexity (AOTC) of an orthodontic case and malocclusion characteristics. METHODS: Two groups of orthodontists (groups A and B) were asked to define perceived treatment complexity (PTC) of orthodontic cases based on 16 characteristics of malocclusion by means of a questionnaire. Each question was answered on a six-point ordinal scale, with one "not applicable" option (score 0). Group A was also asked to give the AOTC of the specific case on a five-point ordinal scale. The index of orthodontic treatment need (IOTN) score of the specific cases as well as the malocclusion characteristics were assessed by one author. RESULTS: There is a significant relationship between IOTN and AOTC (p< 0.0001), 22% of variability is explained by differences in IOTN. Adding objective characteristics of malocclusion to explain AOTC does not significantly increase the explained variability (p = 0.086). In judging interobserver agreement, a weighted Kappa of 0.60 for group A and 0.56 for group B was found. The weighted Kappa for agreement in AOTC equals 0.06. CONCLUSION: The relation between IOTN and AOTC was found to be significant. Moderate agreement on PTC among observers and a low level agreement regarding AOTC were found in the present study.